Bifurcated Current Sheet Observed on the Boundary of Kelvin-Helmholtz Vortices - Hwang, K-J.; Dokgo, K.; Choi, E.; Burch, J. L.; Sibeck, D. G.; Giles, B. L.; Norgren, C.; Nakamura, T. K. M.; Graham, D. B.; Khotyaintsev, Y.; Shi, Q. Q.; Gershman, D. J.; et al. (Frontiers in Astronomy and Space Sciences, 2021)
On May 5, 2017 MMS observed a bifurcated current sheet at the boundary of Kelvin-Helmholtz vortices (KHVs) developed on the dawnside tailward magnetopause. We use the event to enhance our understanding of the formation and structure of asymmetric current sheets in the presence of density asymmetry, flow shear, and guide field, which have been rarely studied. The entire current layer comprises three separate current sheets, each corresponding to magnetosphere-side sunward separatrix region, central near-X-line region, and magnetosheath-side tailward separatrix region. Two off-center structures are identified as slow-mode discontinuities. All three current sheets have a thickness of ∼0.2 ion inertial length, demonstrating the sub-ion-scale current layer, where electrons mainly carry the current. We find that both the diamagnetic and electron anisotropy currents substantially support the bifurcated currents in the presence of density asymmetry and weak velocity shear. The combined effects of strong guide field, low density asymmetry, and weak flow shear appear to lead to asymmetries in the streamlines and the current-layer structure of the quadrupolar reconnection geometry. We also investigate intense electrostatics waves observed on the magnetosheath side of the KHV boundary. These waves may pre-heat a magnetosheath population that is to participate into the reconnection process, leading to two-step energization of the magnetosheath plasma entering into the magnetosphere via KHV-driven reconnection.